Second-Language Skills for All? Analyzing a Proposed Language Requirement for U.S. Air Force Officers - Hardison, Chaitra M. (RAND Corporation, 2012)
In an effort to determine the feasibility of requiring all Air Force officers to attain a specific level of proficiency in a second language, the authors conducted a survey of current Air Force officers. The results suggest that such a requirement is not currently feasible. However, it would instead be desirable to offer incentives for a variety of efforts made toward achieving proficiency, both before and after commissioning.